Without children : the long history of not being a mother - O'Donnell Heffington, Peggy (Seal Press, Hachette Book Group, 2023)
"From Joan of Arc to Queen Elizabeth I, to Harriet Tubman and Susan B. Anthony, to Sally Ride and Jennifer Aniston, history is full of women without children. Some chose to forgo reproduction in order to pursue intellectually satisfying work--a tension noted by medieval European nuns, 1970s women's liberationists, and modern professionals alike. Some refused to bring children into a world beset by famine, pollution, or climate change. For others, childlessness was involuntary: infertility has been a source of anguish all the way back to the biblical Hannah. But most women without children didn't--and don't--perceive themselves as either proudly childfree or tragically barren. Seventeenth century French colonists in North America, struggling without the kind of community support they enjoyed in their mother country, found themselves postponing children until a better moment that, for many of them, never arrived. It is women like these--whose ambivalence throughout their child-bearing years inevitably makes their choice for them--that make up the vast majority of millennials without children in the United States. Drawing on deep archival research and her own experience as a woman without children, historian Peggy O'Donnell shows modern women who are struggling to build lives and to figure out whether those lives allow for children that they are part of a long historical lineage-and that they are certainly not alone"--